Relevansi Konsep Merdeka Belajar dengan Nilai-Nilai Filosofis Pendidikan Di SMA INS Kayu Tanam - Marjanis, Marjanis (JOEAI (Journal of Education and Instruction), 2021)
The purpose of writing this article is to determine the relevance of the concept of independent learning to the philosophical values ​​of education at SMA INS Kayu Tanam. In particular, this article examines the conception of Sjafe'i's educational thinking that he applied to the school he founded, Ruang Pendidik INS Kayutanam. The analysis was carried out in a qualitative descriptive manner by reviewing various articles and relevant sources to reveal the principles of INS Kayu Tanam that are timeless even though time has passed almost 100 years. The results show that although it has been established since the Dutch colonial era in 1926, the principles that underlie the implementation of the INS Kayutanam education system can survive despite several changes in Indonesian education policies and curriculum. In fact, the principles voiced by Mohammad Sjafe'I can be applied to support the Free Learning program which is currently being echoed by the government. In conclusion, the spirit of learning independence has existed since INS Kayutanam was established. The independence that is relevant in the context of current conditions is of course how teachers and students as well as independent educational institutions carry out quality education to create students with character, skills and have the ability to think critically and reason well. Keywords: INS Kayu Tanam, Education System Policy, Independent Learning